An Analysis of Students’ Ability to Identify Main Ideas and Supporting Ideas in Narrative Texts at SMA Muhammadiyah Bangkinang - Rafika Makhiro; Putri Asilestari; Masrul Masrul (Institut Teknologi Pendidikan Indonesia, 2026)
This research aims to analyze the students’ ability and difficulties in identifying the main idea and supporting ideas in narrative texts at SMA Muhammadiyah Bangkinang, particularly the students of class X.4 in the 2024/2025 academic year. This research employed a descriptive qualitative method. The subjects of this research consisted of 30 students of class X.4. The data were collected through a reading comprehension test in the form of 25 multiple-choice questions and documentation. The instrument was developed based on five reading indicators: word meaning, meaning in context, main idea, text relationship, and analyzing process. The results of the research showed that students still experienced various difficulties in understanding narrative texts. The highest percentage of errors was found in the indicator of meaning in context (43.92%), followed by analyzing process (26.35%), main idea (11.71%), word meaning (10.36%), and text relationship (7.66%). These findings indicate that most students had difficulty in understanding contextual meaning and analyzing the structure of narrative texts. These difficulties were caused by limited vocabulary mastery, lack of reading strategies, minimal reading practice, and low confidence in comprehending the text. Based on the findings, it can be concluded that the students’ ability to identify the main idea and supporting ideas in narrative texts is still categorized as low. Therefore, teachers are suggested to apply more effective reading strategies and provide continuous reading practice to improve students’ reading comprehension skills. This research is expected to contribute to the development of reading instruction and serve as a reference for future researchers who conduct similar studies.